Impact of Service Quality on Business Sustainability: A Mediation-Moderation Prospective - Adnan, Muhammad; Rashid, Muhmmad; Khan , Sajjad Nawaz; Baig, Fahad Javed (Pakistan Journal of Humanities and Social Sciences, 2023)
Current study explores the elaborate relationship between customer service quality, customer retention, relationship marketing, and business sustainability of the banking sector. The basic aim of current research is to discover how customer retention mediates the relationship between customer service quality and business sustainability, while also investigating the moderating influence of relationship marketing. A survey questionnaire research strategy was used in this study along with a simple random sampling of 300 banking sector of South Punjab Pakistan. For data analysis, this research used the p-test based on SPSS. By combining theoretical insights with empirical findings, this study contributes to the expanding literature on customer-centric strategies for sustainable business growth. The implications drawn from this research will equip retail businesses with a more holistic understanding of the dynamics that underpin the nexus between customer service quality, customer retention, relationship marketing, and business sustainability. Ultimately, the findings offer practical insights that can guide retail practitioners in optimizing their strategies to not only enhance service quality and customer retention but also to fortify the foundations of their long-term business viability and success.